Efforts to Implement the ABCDE Approach to Difficult Weaning (Indian Journal of Case Reports, 2026)
Weaning patient form mechanical ventilation is a major challenge in intensive care unit. This is because weaning failure increase ventilator use, length of stay, and increasing the risk of infection resulting morbidity dan mortality. A conceptual framework known as ’ABCDE’ is used to evaluate and manage patients who are difficult to wean. , We deliver a case difficult to wean patient 25-year-old woman who referred to hospital due to weaning failure, after being treated in ICU for acute respiratory failure caused by severe pneumonia. Upon arrival at our hospital, a thorough evaluation revealed pleural effusion, hyperthyroidism and psychological issues hindering the patient’s weaning. Thoracocentesis USG guide, a negative cumulative balance, physiotherapy, hyperthyroidism treatment, calorie intake according to patient needs and psychological support from doctors, nurses, physiotherapists and family members were provided. Weaning was gradual, using CPAP and a T-piece. On the ninth day of ICU care, the patient was extubated and discharged on the thirteenth day without any recurrence of respiratory failure. A holistic and structured evaluation using the ‘ABCDE’ approach was useful in identifying the factors causing the difficult weaning and how to manage them